EFFORTS TO IMPROVE STUDENT UNDERSTANDING IN UTILIZING THE EFFICACY AND SAFETY OF TRADITIONAL DRUGS AT SMK PUTRA BANGSA SALATIGA - Ahwan Abdul; Mustaan Mustaan; Anik Suwarni (Universitas Ahmad Dahlan, 2021)
Indonesia is a country that has the most plant biodiversity in the world, so that students and the government can take advantage of this biodiversity in preventing or adding complementary therapies to a disease. This utilization effort can increase the socio-economic level of Indonesian students. This service is carried out to be a solution to provide information and understanding to vocational students about the use, efficacy and safety of medicinal plants to assist the treatment process by utilizing the use of traditional medicinal plants, which schools only receive this information. So that vocational school graduates can later open their own business in the development of traditional medicines by knowing in advance the benefits, properties and safety of these traditional medicines. The method used in this service is through providing information on medicinal plants that are used as a preventive and promotive effort in treating existing diseases. This service is carried out to provide benefits, efficacy and safety to students of SMK Putra Bangsa Salatiga. Students get information about how to use medicinal plants in their environment so that they can be used if they have graduated or not